2015
DOI: 10.26687/archnet-ijar.v9i2.792
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: Advancing the Debate on Architecture, Planning, and Built Environment Research

Abstract: With an acceptance rate that does not exceed 25% of the total papers and articles submitted to the journal, IJAR – International Journal of Architectural Research is moving forward to position itself among the leading journals in architecture and urban studies worldwide. As this is the case since the beginning of volume 5, issue 1, March 2011, one must note that the journal has been covered by several data and index bases since its inception including Avery Index to Architectural Periodicals, EBSCO-Current Abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…This is evidenced by the rise of associated techniques in spatial planningfor example, Frank et al, (2014: 75) found 'extensive use of an online, interactive, virtual learning environment'. There is also an alignment of active learning with the communities of learning as a praxis for planning (Cantor et al, 2014;Kallus, in Frank and da Rosa Pires, 2021) and placemaking (Altay, 2014;Salama 2010Salama , 2016.…”
Section: Lucy Natarajan and Michael Shortmentioning
confidence: 99%
“…This is evidenced by the rise of associated techniques in spatial planningfor example, Frank et al, (2014: 75) found 'extensive use of an online, interactive, virtual learning environment'. There is also an alignment of active learning with the communities of learning as a praxis for planning (Cantor et al, 2014;Kallus, in Frank and da Rosa Pires, 2021) and placemaking (Altay, 2014;Salama 2010Salama , 2016.…”
Section: Lucy Natarajan and Michael Shortmentioning
confidence: 99%
“…The research-based learning technology, an active and experiential technological approach [33,34], in architectural education, may also be treated as a part of the blended learning technological approach produced by the blending of different methodologies.…”
Section: Research-based Learning Technologymentioning
confidence: 99%
“…As Salama (2010, p. 278) argues, “recent discourse on built environment education asserts that a course mission should foster a learning environment that nurtures exploration and critical thinking”. This can be achieved by incorporating inquiry-based learning methods into architectural design pedagogy in order to generate active and experiential learning (Salama, 2010, pp. 278-295; Djabarouti and O'Flaherty, 2019, pp.…”
Section: Reflectionsmentioning
confidence: 99%